Focus group-supported development and psychometric exploration of an instrument to assess perceived physical exertion in nursing students - Eva Lorenz; Eva Grüne; Johanna Popp; Klaus Pfeifer; Johannes Carl (BMC Nursing)
Abstract Background The physical demands of nurses during their work and education are high. In addition, shortage in nursing staff increases the individual workload. However, an appropriate tool to measure perceived physical exertion in nursing students is missing. Therefore, the goal of the present study was to design a questionnaire to assess perceived physical exertion in nursing students during their vocational education and to explore its factor structure. Methods We initially conducted two parallel semi-structured focus group interviews with purposefully sampled nursing students to gain insights into their daily physical load. We coded the material and derived an initial set of 35 items (work-related and school-related). Subsequently, we conducted another semi-structured focus group interview with purposefully sampled nursing students of another school to cross-validate the items and refine the preliminary questionnaire according to their responses. To check the psychometric quality and factor structure of the questionnaire, we used data of 237 nursing students from 16 different nursing schools. We analyzed the items (n = 30) descriptively (including internal consistency via Cronbach’s α) and examined the structure of the questionnaire using exploratory factor analyses. Results In the focus group interviews, we found different categories that play a role for perceived physical exertion in nursing vocational education: ‘general conditions’, ‘patient’, ‘additional load’, ‘locomotion’, ‘awkward postures’, ‘one-sided load’ and ‘others’. The factor analyses suggested three factors explaining the structure of the questionnaire. We registered satisfactory item statistics and good internal consistencies for all three factors: ‘relocating and handling of objects’ (α = 0.967); ‘personal care of patients’ (α = 0.910); ‘relocating patients’ (α = .809). The final questionnaire comprises 30 items (28 work-related, two school-related). Conclusion The developed questionnaire provided initial evidence for content validity and internal consistency of the factors. The instrument can be used to detect perceived physical exertion in nursing students and thus help specifically address health-related problems. There is a need for a further confirmatory approach to cross-validate the questionnaire. Trail registration Clinical trials NCT05817396.